Active Power Reserve Estimation of Two Interconnected Microgrids. (May 2017) - Tungadio, Diambomba H.; Bansal, R.C.
Abstract: This paper presents the optimization of active power reserve of two alternating current (ac) interconnected microgrids. The main objective is to meet the power demand completely while satisfying the system constraints. Optimal control theory was used to solve the estimation problem. The active power from all the sources is taken as control variables. The effectiveness of the proposed model is shown through the simulation results of the network model.